Engaging Red River Métis families in Manitoba in the development of child health resources – findings from a qualitative study - Knisley, Lisa; Driedger, S. Michelle; Hartling, Lisa; Chartrand, Frances; Sanguins, Julianne; Scott, Shannon D. (Research Involvement and Engagement, 2025)
Abstract Background Most research that includes Red River Métis tends to be pan-Indigenous. Grouping Métis with First Nations and Inuit can diminish their unique and diverse experiences, as well as distinctions-based approaches. Taking a step toward addressing this problem, the Manitoba Métis Federation (MMF; the national government of the Red River Métis) invited researchers within the Canadian network Translating Emergency Knowledge for Kids to partner in this research, which focuses on understanding engagement strategies that can help expose Red River Métis parents to child health research opportunities and build trust and transparency amongst research partners and participants. Methods A qualitative descriptive approach underpinned by a participatory paradigm guided this study. Semi-structured interviews were conducted with 19 Red River Métis parents and Elders via Zoom or telephone. An inductive thematic analysis approach was used to explore patterns and themes across the data. Results Analysis generated four themes: (a) show me why you are here; (b) make it easier for me to take part; (c) create welcoming spaces; and (d) it should be a give and take experience. Parents emphasized the importance of kinship and personal connections, and said they want to hear about child health study opportunities from trusted organizations. They want researchers to be transparent about their research motivations and to offer multiple ways to participate to help them fit research into their busy lives. Relational approaches within the research process (e.g., creating informal/welcoming environments, gathering over food, fostering shared learning/creative opportunities) are prominent in the findings. Conclusion There is a dearth of research focused on the distinct experiences of Red River Métis families. Engaging Red River Métis parents early in the research process will help incorporate their preferences and perspectives into the design of a larger project to adapt child health resources. More training is needed to help ...